Understanding life-threatening illness – exploring individual experiences of living with cancer. Issue 2 (1st September 2011) - Taplin, Sue
Abstract : "A few decades ago, cancer was a topic shrouded in social silence. Today…stories of cancer illness have found a place in our culture. The emergence of this discourse means that those who become ill with cancer can expect some degree of acceptance and understanding. The same cannot be said, however, about all those who survive cancer. Despite the interest that is often generated by stories of survival…there still remain unresolved tensions for those who have lived beyond the acute phase of extreme experience." This study, which originates from my practice as a social worker in the field of palliative care and formed part of my doctoral studies, sought to uncover and explore some of these 'unresolved tensions' in the lives of those who are experiencing cancer as a long-term condition. I aimed in this study to give individuals who were living 'with and beyond cancer' the opportunity to talk about their experiences, both during the treatment phase and beyond, in order to explore the meaning of this experience, and therefore to increase the body of public and professional knowledge in this field. I conducted semi-structured interviews with 18 people who were living with cancer as a long-term condition, simultaneously analysing these narratives using a grounded theory approach. My findings from this study were that, overwhelmingly, individuals experienced cancer as life-changing, not only in terms of their own personal development and attitudes to life, but also in how they related to the people around them, including health and social care professionals. While recognising the individual nature of each person's experience, the findings of my study have provided an invaluable insight into the psychosocial needs of people living with cancer, which I aim to disseminate to professionals and policymakers, to increase understanding and enhance aftercare in cancer 'survivorship'.